358. 1) a (x - c)+ bc - bx; 2) a (b + c)+ db + de;
3) 3a (2b+c)+86 +4c;
4) 2x (3x - 4y) - 6x+8y.​

Dmitro222 Dmitro222    1   20.01.2021 06:22    3

Ответы
настюшка1101 настюшка1101  19.02.2021 06:25

Надеюсь, правильно

a (x - c)+ bc - bx = ax - ac + bc - bx \\ a (b + c)+ db + de = a + b + c + bd + ed \\ 3a (2b+c)+86 +4c = 3a \times 2b + 3ac + 86 + 4c = 6ab + 3ac + 86 + 4c \\ 2x (3x - 4y) - 6x+8y = 2x \times (3x - 4y) - 2(3x - 4y) = (3x - 4y) \times (2x - 2) = (3x - 4y) \times 2(x - 1) = 2(3x - 4y) \times (x - 1)

ПОКАЗАТЬ ОТВЕТЫ